Estimating the Total and Regional Body Fat of Physically Active Men Is Not Appropriate for Sedentary Men - Silalertdetkul, Supaporn (Physical Education Theory and Methodology, 2024)
Objectives. The reliability of predictive body fat equations remains unclear due to their inappropriate use across different subject cohorts and conditions. The objective of this study was to validate and cross-validate equations to predict total and regional body fat in young physically active males. Material and methods. Three hundred and five young male participants were divided into the following groups: active validation (n=165), active cross-validation (n=70), or sedentary cross-validation ones (n=70). The study used a stratified random sampling based on weekly physical activity level. The total and regional body fat mass were measured using dual-energy X-ray absorptiometry (DEXA) after an overnight fast. Simultaneous measurements of height, body mass, skinfold thickness, body mass index, and body circumferences were taken. The total and regional body fat predictive equations were generated using multiple linear stepwise regression models. The coefficient of determination (R²) and standard error of estimation (SEE) were calculated to examine the accuracy of the predictive equations. Furthermore, cross-validation groups were analysed. Results. The percentage of total body fat, trunk fat, legs fat, arms fat, and body mass index of active cross-validation were found to be significantly lower than in the sedentary cross-validation groups. The total body fat percentage was highly associated with abdominal skinfold thickness (R=0.68-0.74, P<0.001), body mass index (R=0.55, P<0.001), and suprailiac skinfold thickness (R=0.67-0.71, P<0.001) in the active validation group. The predictive total and regional body fat equations of physically active men showed adjusted R² values ranging from 0.35 to 0.66, with standard error of estimation values between 2.74 to 4.35%. The standard error of estimation for the predictive percentage of total and regional body fat in the active cross-validation group was lower than in the sedentary cross-validation group. Conclusions. The findings demonstrate that new predictive total and regional body fat equations can be used to accurately estimate body fat in healthy young active males under fast conditions.